Pengaruh Kepemimpinan Dan Kedisiplinan Terhadap Kinerja Perangkat Kelurahan Sekecamatan Sukoharjo Kabupaten Sukoharjo Dengan Motivasi Sebagai Variabel Mediasi - Wati, Mamik Hirna (-)
This study aims to identify and analyze the influence of leadership and discipline on the performance of the device villages Sekecamatan Sukoharjo Sukoharjo regency with motivation as Variable Mediation. The analysis technique used is to use a test instrument that includes the validity and reliability test, linearity test, regression analysis, path analysis (Path Analysis), t test, F test, test the coefficient of determination and correlation analysis. The results showed that leadership and significant positive effect on the motivation. Discipline and no significant positive effect on the motivation. Leadership positive and significant impact on performance. Discipline positive and significant impact on performance. Motivation positive and significant impact on performance. The F test results can be concluded jointly variables of leadership, discipline and motivation have a significant effect on performance. The result of the calculation of total R2 value of 0.89 can be interpreted variations in device performance villages sekecamatan Sukoharjo explained by leadership, discipline and motivation by 89% and the remaining 11% described other variables outside the model as an example of climate research organization and competence. Conclusion Effect of Direct and Indirect illustrates that the direct effect on the performance leadership and discipline produces a value greater than the indirect effect. Making it more effective through the direct route. Discipline is the most dominant variable in improving device performance villages Sekecamatan Sukoharjo district.Â Keywords: Leadership, Discipline, Motivation, Performance